2013
DOI: 10.1071/fp13074
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of halophytes to multiple stresses

Abstract: As halophytes grow vigorously in saline soils, they serve as extraordinary resources for the identification and development of new crop systems. Understanding the mechanisms of tolerance of halophytes to salinity in combination with other co-occurring constraints such as drought, flooding, heavy metals and nutrient deficiencies, would facilitate efforts to use halophytes for saline land revegetation, as well as provide new insights that might be considered in future breeding of plants for salt-affected agricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 111 publications
3
55
0
Order By: Relevance
“…It was well-known tolerance to salinity and drought as often positively correlated with an effective antioxidant system. [21,[25][26][27] The halophyte species studied in this work were native of stressful biotopes and have acquired adaptation strategies, particularly against oxidative stress, by high activity of antioxidant enzymes if compared to glycophytes plants. Thus, our results suggested that L. vulgare, native to Oued Rane, had a cell protection better than other species by the high SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…It was well-known tolerance to salinity and drought as often positively correlated with an effective antioxidant system. [21,[25][26][27] The halophyte species studied in this work were native of stressful biotopes and have acquired adaptation strategies, particularly against oxidative stress, by high activity of antioxidant enzymes if compared to glycophytes plants. Thus, our results suggested that L. vulgare, native to Oued Rane, had a cell protection better than other species by the high SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major consequences of salt stress is a disruption of Na + and K + homeostasis in both cellular and whole-plant levels, accompanied by membrane dysfunction and attenuation of cellular metabolism, resulting in the inhibition of cell division, growth, photosynthesis, and development (Omielan et al, 1991; Flowers, 1999; Horie and Schroeder, 2004; Yan et al, 2013; Duan et al, 2015). To avoid Na + toxicity, plants have evolved various adaptation mechanisms, such as restricting Na + uptake from environments, extruding cytoplasmic Na + to the outside of the cell and sequestering Na + into vacuoles to reduce Na + accumulation in cytosol (Wang et al, 2007; Hamed et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In salt deserts of the arid and semiarid regions, particularly at Chott and Sebkhas, soil is a source of salt particles easily carried by the wind towards the land and surrounding cultures (Mtimet 2001). Thus, plants in these environments have certainly acquired characteristics to adapt to soils whose chemical composition varies in time and space, depending on salinity and associated stress (Ben Hamed et al 2013). Therefore, the adaptations of these coastal plants are complex and varied.…”
Section: Introductionmentioning
confidence: 99%